Credibility and Market Fitness Drive Perceived Product Value in Iraqi Startups: Kredibilitas dan Kesesuaian Pasar Mempengaruhi Nilai Produk yang Dirasakan pada Startup Irak - Zaid Yaseen Saud (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In volatile and resource-constrained markets, marketing foresight has emerged as a strategic capability that enables firms to anticipate change and align offerings with consumer expectations. Specific Background: While extensively studied in developed economies, the role of marketing foresight in shaping perceived product value within emerging markets remains underexplored. Knowledge Gap: Limited empirical evidence exists on how the specific dimensions of marketing foresight—novelty, executability, credibility, market fitness, and commercial feasibility—affect customers’ value perception in Iraqi start-ups. Aims: This study investigates the impact of foresight dimensions on perceived product value, identifying which dimensions exert the greatest influence. Results: Using survey data from 125 employees in consumer-based start-ups in Baghdad and employing regression analysis, findings reveal that credibility and market fitness significantly enhance perceived product value, while novelty and executability show weaker effects, and commercial feasibility has only marginal influence. Novelty: By empirically disentangling the relative contributions of foresight dimensions in an unstable emerging-market context, this study challenges the assumption that novelty is the primary driver of value creation. Implications: The results highlight that in environments marked by uncertainty, trust and market alignment outweigh radical innovation, offering valuable insights for start-ups and policymakers to prioritize credibility, customer-centric alignment, and incremental innovation for sustainable competitiveness. Highlights: Credibility and market fitness are the strongest predictors of product value. Novelty and executability have weaker, non-significant effects. Consumers in volatile markets prioritize trust and alignment over radical innovation. Keywords: Marketing Foresight, Perceived Value, Credibility, Market Fitness, Start-up